Acute myeloid leukemia in the pregnant patient. (18th April 2015) - Thomas, Xavier
Abstract Although acute myeloid leukemia (AML) mostly occurs in older patients, it could be seen in women of childbearing age. It is therefore not surprising that in some patients, the management of AML will be complicated by a coexistent pregnancy. However, the association of leukemia and pregnancy is uncommon. Its incidence is estimated to be 1 in 75 000–100 000 pregnancies. During pregnancy, most leukemias are acute: two‐thirds are myeloid and one‐third are lymphoblastic. There is no standard approach for this clinical dilemma, in part because of variables such as the type of AML, the seriousness of the symptoms, and the patient's personal beliefs. In many cases, the diagnostic workup has to be altered because of the pregnancy, and often available treatments have varying risks to the fetus. While chemotherapy is reported to have some risks during the first trimester, it is admitted that it can be administered safely during the second and the third trimesters.